Staging lymphadenectomy in renal cell carcinoma must be extended: a sensitivity curve analysis. (15th June 2012) - Capitanio, Umberto; Suardi, Nazareno; Matloob, Rayan; Abdollah, Firas; Castiglione, Fabio; Briganti, Alberto; Carenzi, Cristina; Roscigno, Marco; Montorsi, Francesco; Bertini, Roberto
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? In renal cell carcinoma the role of lymphadenectomy (LND) is still controversial. Moreover, no firm consensus exists regarding the minimum number of lymph nodes that should be removed to obtain a satisfactory staging LND at the time of surgery. Our findings demonstrate that, when clinically indicated, staging LND in renal cell carcinoma should be extended. The removal of 15 lymph nodes might represent the lowest threshold to define a staging LND as adequate. More extended LND should be pursued if unfavourable clinical and pathological characteristics are evident at diagnosis and/or during surgery. Objective To investigate the staging of lymphadenectomy in renal cell carcinoma. No convincing data exist regarding the minimum number of lymph nodes that should be removed at the time of nephrectomy to ensure an accurate staging. Methods Between 1987 and 2011, 850 patients with renal cell carcinoma underwent either partial or radical nephrectomy plus lymph node dissection (LND) at a single tertiary care institution (TanyN0–1Many). Receiver operating characteristic curve coordinates were used to graph the probability of finding lymph node invasion according to the number of removed lymph nodes. Assuming that the likelihood of finding lymph node invasion according to the number of lymph nodes removed may be affected by patient characteristics, analyses were further stratified for clinical and pathological characteristics. Results The rate of lymph node metastases strongly correlated with the clinical and pathological characteristics of the patients. Fifteen lymph nodes need to be removed to achieve a 90% probability of detecting at least one metastatic lymph node. Only slight differences were recorded after stratification for clinical nodal status, the presence of metastases at diagnosis and pathological T stage. Finally, 13, 16 and 21 lymph nodes need to be removed to achieve a 90% probability of detecting lymph node invasion, if present, in the low risk (score 0–1), intermediate risk (score 2–3) and high risk (score 4–5) Mayo Clinic classification, respectively. Conclusion The removal of 15 lymph nodes represents the lowest threshold for considering a staging LND as adequate. More extended LND should be pursued if unfavourable clinical and pathological characteristics are evident at diagnosis and/or during surgery.